Music Trouble: Desire, Discourse, Education - Lamb, Roberta (Canadian University Music Review / Revue de musique des universités canadiennes, 1997)
"Music Trouble" is an experimental paper, a linear re-presentation of the multi-media performance (which included costume, poetry, photographs, and musical scores, in addition to the paper) designed for the Ottawa Border Crossings Conference. "Music Trouble" explores identity construction through music and music education, specifically in relation to issues of sexuality. Judith Butler's idea of "gender is drag" and Sue-Ellen Case's "butch-femme aesthetic" are employed in conjunction with feminist auto/biography to critique current theories and practices supporting music education.